Potassium tert-Butoxide Mediated Reductive C–P Cross-Coupling of Arylvinyl Sulfides through C–S Bond Cleavage - Feng, Jie; Zhang, Qiaoling; Li, Fuhai; Yang, Lu; Kuchukulla, Ratnakar Reddy; Zeng, Qingle (Synlett, 2020)
A transition-metal-free t-BuOK-mediated reductive C–P cross-coupling reaction of arylvinyl sulfides with diarylphosphine oxides through C–S bond cleavage has been developed. This protocol not only permits the synthesis of diaryl(2-arylethyl)phosphine oxides, but also achieves an unprecedented construction of a C–P bond through C–S bond cleavage and reduction of a C–C double bond in one pot.
Keywords: alkenyl sulfides; C–S bond cleavage; C–P bond formation; potassium butoxide; transition-metal-free synthesis